Struggles of vehicle residents in Squamish: Challenging the capitalist and colonial institution of housing - Thomasina Pidgeon; Ana Vilenica (Radical Housing Journal)
In this conversation, Thomasina Pidgeon discusses her decision to live in a vehicle in Squamish, north of Vancouver, in British Columbia, Canada. This was a choice originally driven by the lack of affordable housing, but she continued with it after falling in love with life on the road. Her story sheds light on the broader issues of housing, gentrification, and societal attitudes toward non-sedentary life choices. For Thomasina, living in a vehicle offered a sense of freedom for her and her daughter, despite occasional problems, as well as a deep connection with nature that conventional housing couldn’t provide. However, as Squamish has grown more gentrified, particularly after the 2010 Olympics, the town has increasingly cracked down on vehicle residents, categorising them as unhoused and treating them as a problem. These restrictive regulations, according to Thomasina, are part of a larger system that prioritizes property values and profits over human needs, echoing colonial practices that forced nomadic communities to settle for the benefit of those in power. Her story calls for a shift in how we think about housing, urging us to go beyond housing as a capitalist and colonial institution, and towards a deeper understanding of the systemic issues that lead to the so-called housing crisis. Despite facing stress and anxiety due to these crackdowns, Thomasina continues to advocate for the rights of vehicle residents with the organization Vehicle Residents of Squamish, and to connect different struggles from Palestinian solidarity work to struggles against an LNG terminal.